Stimulation of exocrine pancreatic secretion by met-enkephalin. Issue 12 (December 1986) - Gullo, L; Priori, P; Baldoni, F; Mattioli, G
Abstract : The effect of met-enkephalin on pure exocrine pancreatic secretion was studied in five subjects with external transduodenal drainage of the main pancreatic duct carried out after biliary tract surgery. Intravenous infusion of a low dose of met-enkephalin (0.15 micrograms/kg/h) during submaximal pancreatic stimulation with secretin (25 ng/kg/h) and cerulein (10 ng/kg/h) significantly increased pancreatic outputs. Bicarbonate secretion increased 50% above control values, a more marked effect than the increase in enzyme secretion (maximal rise averaged 22%). The effect of the peptide was rapid, persisted for the duration of met-enkephalin infusion and then tended gradually to diminish.